Reactive arthritis complicating cryptosporidial infection. - Shepherd, R C (1989)
Two cases of reactive arthritis in association with cryptosporidial enteritis in childhood are reported. Oocysts of cryptosporidium should be sought when arthritis complicates diarrhoeal illnesses.